2009
DOI: 10.1159/000265556
|View full text |Cite
|
Sign up to set email alerts
|

Studying Regression of Seborrheic Keratosis in Lichenoid Keratosis with Sequential Dermoscopy Imaging

Abstract: Background: Lichenoid keratosis (LK) is a well-described entity that has been proposed to represent a regressive response to a pre-existent epidermal lesion. Aims: To evaluate the natural evolution of a series of cases showing the intermediate stage of the regression of seborrheic keratosis in LK using sequential dermoscopy imaging over time. Material and Methods: A series of lesions with dermoscopic areas of seborrheic keratosis and LK in the same tumor were consecutively collected for over 3 years at the Der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…We also showed that the granular pattern dots in the LK lesion histopathologically corresponded to melanin granules in the dermis owing to pigment incontinence . Longitudinal dermoscopic observation revealed that while areas displaying the granular pattern gradually increased, those with common dermoscopic findings of SK, such as comedo‐like openings, milia‐like cysts, fissures and ridges, and hairpin vessels, became decreased in regressing SK lesions . These observations suggest that some forms of LK may represent SK in the process of regression.…”
Section: Dermoscopic Features Of Histopathological Variants Of Sksupporting
confidence: 52%
“…We also showed that the granular pattern dots in the LK lesion histopathologically corresponded to melanin granules in the dermis owing to pigment incontinence . Longitudinal dermoscopic observation revealed that while areas displaying the granular pattern gradually increased, those with common dermoscopic findings of SK, such as comedo‐like openings, milia‐like cysts, fissures and ridges, and hairpin vessels, became decreased in regressing SK lesions . These observations suggest that some forms of LK may represent SK in the process of regression.…”
Section: Dermoscopic Features Of Histopathological Variants Of Sksupporting
confidence: 52%
“…Various paraneoplastic syndromes of the skin are associated with underlying malignancies as observed in reactive erythemas (necrolytic migratory erythema), musculoskeletal disorders (dermatomyositis, hypertrophic osteoarthropathy, clubbing), vascular dermatoses (Trousseau syndrome) and papulosquamous disorders (acanthosis nigricans, Bazex syndrome, and extramammary Paget disease) [4]. These paraneoplastic dermatoses usually disappear following tumor removal in about one-half of the patients and are seen to manifest coincidentally with tumor diagnosis [8]. In our patient, Leser-Trélat syndrome can be considered to have set in 11 years prior when the patient developed a breast lump which was subsequently evaluated and managed [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, states of irritation or regression (in which the seborrheic keratosis is termed a lichenoid keratosis) may mask a clear clinical diagnosis. In these situations, seborrheic keratoses may be mistaken for melanocytic lesions, making the differentiation from melanoma, Bowen’s disease or superficial basal cell carcinoma challenging on both clinical and dermatoscopic levels [1,2]. Zaballos et al has clearly established dermatoscopy as a useful tool to assists in the correct clinical recognition of LK and track the pathogenesis of these tumors by demonstrating the intermediate stages of epidermal regression.…”
Section: Discussionmentioning
confidence: 99%